Single-cell analysis reveals that Jinwu Gutong capsule attenuates the inflammatory activity of synovial cells in osteoarthritis by inhibiting AKR1C3 - Guo, Junfeng; Tang, Chuyue; Shu, Zhao; Guo, Junfeng; Tang, Hong; Huang, Pan; Ye, Xiao; Liang, Taotao; Tang, Kanglai (Frontiers in Physiology, 2022)
Jinwu Gutong capsule (JGC) is a traditional Chinese medicine formula for the treatment of osteoarthritis (OA). Synovitis is a typical pathological change in OA and promotes disease progression. Elucidating the therapeutic mechanism of JGC is crucial for the precise treatment of OA synovitis. In this study, we demonstrate that JGC effectively inhibits hyperproliferation, attenuates inflammation, and promotes apoptosis of synovial cells. Through scRNA-seq data analysis of OA synovitis, we dissected two distinct cell fates that influence disease progression (one fate led to recovery while the other fate resulted in deterioration), which illustrates the principles of fate determination. By intersecting JGC targets with synovitis hub genes and then mimicking picomolar affinity interactions between bioactive compounds and binding pockets, we found that the quercetin-AKR1C3 pair exhibited the best affinity, indicating that this pair constitutes the most promising molecular mechanism. In vitro experiments confirmed that the expression of AKR1C3 in synovial cells was reduced after JGC addition. Further overexpression of AKR1C3 significantly attenuated the therapeutic efficacy of JGC. Thus, we revealed that JGC effectively treats OA synovitis by inhibiting AKR1C3 expression.